Healthy eating index and anthropometric status in young children: A cross-sectional study. (October 2021) - Askari, Mohammadreza; Daneshzad, Elnaz; Naghshi, Sina; Bellissimo, Nick; Suitor, Katherine; Azadbakht, Leila
Summary: Background & aims: Weight status and growth during childhood are indicative of healthy development throughout the lifespan. Thus, understanding the influence of overall quality of diet and dietary patterns on anthropometric measures during childhood is critical to inform dietary recommendations. The current study used an updated version of the healthy eating index (HEI) to evaluate the association between overall diet quality and measures of childhood development in six-year-old children. Methods: This cross-sectional study was conducted across 788 six-year-old children referred to healthcare centers in Tehran, Iran. Anthropometric indices and dietary intake were evaluated using standard protocols and food frequency questionnaires, respectively. The HEI-2015 was used to evaluate participant diet quality. The total HEI-2015 score ranged from zero to 100 using the sum of thirteen food score components. Results: Children in the highest tertile of HEI score had higher nutrient intakes and HEI-related food groups ( p  < 0.05). Children within the highest tertile of HEI score compared to those within the lowest tertile were more likely to be overweight (OR: 1.45; 95% CI = 1.01; 2.08). Conclusions: Findings presented in this study showed that HEI was not associated with a greater likelihood of obesity, underweight, severe underweight, and stunting. However, children in the highest tertile of HEI score were more likely to be overweight.